أثر استخدام الجنس في الإعلان في اتجاهات المستهلك " دراسة مسحية " - شيخ ديب, صلاح; قاسم, سامر; زيداني, عبير (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يهدف هذا البحث إلى تحليل ظاهرة استخدام الجنس في الإعلان، حيث يقوم الكثير من المُعلنين باستخدام الجنس في الإعلان بهدف جذب انتباه المستهلك للإعلان في ظل فوضى الإعلانات التي يتعرّض لها المستهلك, كما يهدف هذا البحث إلى تسليط الضوء على إيجابيات وسلبيات استخدام الجنس في الإعلان وذلك من خلال الرجوع إلى الأدبيّات التي تناولت موضوع استخدام الجنس في الإعلان, كما يهدف هذا البحث من خلال الجانب العملي إلى قياس أثر استخدام الجنس (المغريات الجنسية) في الإعلان على اتجاه المستهلك نحو الإعلان ونحو العلامة التجارية المُعلن عنها وذلك باختلاف جنس المستهلك, خلصت الدّراسة إلى أنّ استخدام الجنس في الإعلان يؤثّر بشكل إيجابي قي اتجاهات المستهلكين الذكور نحو الإعلان ونحو العلامة التجارية المُعلن عنها, وأنّ استخدام الجنس في الإعلان يؤثّر بشكل سلبي في اتّجاهات المستهلكات نحو الإعلان ونحو العلامة التجارية المُعلن عنها’ بناءً على النتائج اقترح الباحثون استخدام الجنس (المغريات الجنسية) في الإعلان الموجّه للذكور وتجنّب استخدام الجنس في الإعلان الموجّه للإناث بهدف خلق اتجاهات إيجابية نحو الإعلان ونحو العلامة التجارية المُعلن عنها. This research consists of two parts. The first part depends on the previous researches and literature dealing with the subject research "sex in advertising". This research aims through the first part to analyze "sex in advertising" phenomenon, since advertisers use sex in advertising to attract the consumer to the advertisement. This research through field study aims to measure the effect of sex in advertising on the consumer's attitude toward advertising and towards brand according to the consumer's gender. Through survey study, the research shows that there is a positive effect of sex in advertising on the consumer's attitude towards advertising and brand: when the consumers are male, whereas there is a negative effect of sex in advertising on the consumer's attitude towards advertising and brand when the consumers are females. Based on the findings, researchers suggest that advertisers can use sex in advertising to create a positive attitude toward advertising and brand when the consumers are males, and avoid using sex in the advertising addressed to female consumers with the aim to gain positive attitude towards both advertising and brand.